2004
DOI: 10.1097/00042728-200410000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Combined Nonablative Skin Rejuvenation with the 595- and 1450-nm Lasers

Abstract: BACKGROUND. Histologic findings are not echoed in the visible effect in the epidermis after skin rejuvenation. SUBJECTS AND METHODS. Ten women (Group A) received five treatment sessions with a 595-nm pulsed dye laser immediately followed by a 1450-nm diode laser. Two other demographically similar groups of 10 patients each, Groups B and C, were treated with the 595-nm pulsed dye laser or the 1450-nm diode laser alone, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…Several skin chromophores are targeted in this kind of approach, with good results. However, a lower fluency must be used with each device to reduce the adverse effects associated with cumulative heat generation …”
Section: Discussionmentioning
confidence: 99%
“…Several skin chromophores are targeted in this kind of approach, with good results. However, a lower fluency must be used with each device to reduce the adverse effects associated with cumulative heat generation …”
Section: Discussionmentioning
confidence: 99%
“…(1) However, the ablative approach is associated with severe side effects and a prolonged patient downtime while nonablative resurfacing with single wavelength light sources has proved less effective than hoped , (2,3) although combinations of wavelengths have recently proved much more effective. (4,5) Both ablative and nonablative skin rejuvenation methods demand the deposition of thermal damage in the upper dermis. In cases with less severe photo-and chronological ageing sequelae, it is possible that a much less invasive and virtually athermal reaction could be very effective, based on the photobiomodulation of target skin cells which leads to the enhanced deposition of collagen and related materials.…”
Section: Introductionmentioning
confidence: 99%
“…42 Trelles et al also showed a nonablative rejuvenating effect with both the 595-nm and 1450-nm lasers used singly, but showed enhanced benefit when the two lasers were used sequentially in the same treatment session. 43…”
Section: The 1450-nm Diode Lasermentioning
confidence: 99%